The English Influence in Iceland. A Diary Study - Kristín Birta Jónsdóttir 1982- (2016)
In recent years, there has been a dramatic increase in the amount of English encountered by Icelandic children, making it a subject in need of further study. This essay presents the finding of an ethnographic diary study on the amount of English exposure of four Icelandic children, at various ages, within their native language community. The purpose of this research is to estimate the amount, and type, of English encountered, by the children, during the course of one week. In order to get a true estimate of the amount and type of English exposure, the study was conducted in the children’s natural surroundings. Data was collected through the use of background surveys, diary studies and interviews. The first part of this essay, presents current studies on language acquisition as well as recent developments in the amount and type of English exposure within the Icelandic community. These developments, have led to an increase in the use and exposure of English in Iceland at present time. The findings of the study indicate that English encountered by Icelandic children is largely receptive in nature. The study also found, that with increased age the children were less likely to watch television and more likely to enjoy online material in English, without the use of Icelandic subtitles. Similarly, the study found that time spent with family members reduced the children’s online English encounters, which speaks to the importance of family in the acquisition of language and its maintenance. Lastly, the study shows how the younger generation in Iceland has adapted to advances in technology more rapidly than the older members of society. As a result, the younger generation currently lives a lifestyle that encourages frequent use of English. Therefore, the amount and nature of English encountered by Icelandic children is a field of study in need of further investigation.